Internet and Distributed Computing Systems 9th International Conference, IDCS 2016, Wuhan, China, September 28-30, 2016, Proceedings - Li, Wenfeng; Ali, Shawkat; Lodewijks, Gabriel; Fortino, Giancarlo; Di Fatta, Giuseppe; Yin, Zhouping; Pathan, Mukaddim; Guerrieri, Antonio; Wang, Qiang (Information Systems and Applications, incl. Internet/Web, and HCI, 2016)
This book constitutes the proceedings of the 9th International Conference on Internet and Distributed Computing Systems, IDCS 2016, held in Wuhan, China, in September 2016. The 30 full papers and 18 short papers presented in this volume were carefully reviewed and selected from 78 submissions. They were organized in topical sections named: body sensor networks and wearable devices; cloud computing and networking; distributed computing and big data; distributed scheduling and optimization; internet of things and its application; smart networked transportation and logistics; and big data and social networks.